Clinical and molecular epidemiology of Crimean-Congo hemorrhagic fever in Oman. - Seif S Al-Abri; Roger Hewson; Hanan Al-Kindi; Idris Al-Abaidani; Amina Al-Jardani; Amal Al-Maani; Samira Almahrouqi; Barry Atkinson; Adil Al-Wahaibi; Bader Al-Rawahi; Shyam Bawikar; Nicholas J Beeching (Public Library of Science (PLoS), 2019)
Background Crimean-Congo hemorrhagic fever (CCHF) is a serious disease with a high fatality rate reported in many countries. The first case of CCHF in Oman was detected in 1995 and serosurveys have suggested widespread infection of humans and livestock throughout the country. Methodology Cases of CCHF reported to the Ministry of Health (MoH) of Oman between 1995 and 2017 were retrospectively reviewed. Diagnosis was confirmed by serology and/or molecular tests in Oman. Stored RNA from recent cases was studied by sequencing the complete open reading frame (ORF) of the viral S segment at Public Health England, enabling phylogenetic comparisons to be made with other S segments of strains obtained from the region. Findings Of 88 cases of CCHF, 4 were sporadic in 1995 and 1996, then none were detected until 2011. From 2011-2017, incidence has steadily increased and 19 (23.8%) of 80 cases clustered around Eid Al Adha. The median (range) age was 33 (15-68) years and 79 (90%) were male. The major risk for infection was contact with animals and/or butchering in 73/88 (83%) and only one case was related to tick bites alone. Severe cases were over-represented: 64 (72.7%) had a platelet count < 50 x 109/L and 32 (36.4%) died. There was no intrafamilial spread or healthcare-associated infection. The viral S segments from 11 patients presenting in 2013 and 2014 were all grouped in Asia 1 (IV) lineage. Conclusions CCHF is well-established throughout Oman, with a single strain of virus present for at least 20 years. Most patients are men involved in animal husbandry and butchery. The high mortality suggests that there is substantial under-diagnosis of milder cases. Preventive measures have been introduced to reduce risks of transmission to animal handlers and butchers and to maintain safety in healthcare settings.